A Randomized Trial of Protocol-Based Care for Early Septic Shock - YEALY, Donald M; KELLUM, John A; FILBIN, Michael R; SHAPIRO, Nathan I; ANGUS, Derek C; HUANG, David T; BARNATO, Amber E; WEISSFELD, Lisa A; PIKE, Francis; TERNDRUP, Thomas; WANG, Henry E; HOU, Peter C; et al. (The New England journal of medicine, 2014)
In septic shock, the first few hours of care are critical for survival. In this study, two protocols for the care of patients with septic shock were compared with usual care with respect to 60-day mortality and other outcomes. There were no significant differences in outcome. There are more than 750,000 cases of severe sepsis and septic shock in the United States each year. 1 Most patients who present with sepsis receive initial care in the emergency department, and the short-term mortality is 20% or more. 2 , 3 In 2001, Rivers et al. reported that among patients with severe sepsis or septic shock in a single urban emergency department, mortality was significantly lower among those who were treated according to a 6-hour protocol of early goal-directed therapy (EGDT) than among those who were given standard therapy (30.5% vs. 46.5%). 4 On the basis of the premise that usual care . . .